Антропогенна трасформація природних ценофлор Кам'янецького Придністров’я (Хмельницька обл.) - Ковтун, І.В. (Промышленная ботаника, 2003)
The paper deals with the results of analysis of influence of adventive plants invasion in native cenofloras upon the Kamiyanetske Prydniestroviya.